2015
DOI: 10.1177/2050312114566668
|View full text |Cite
|
Sign up to set email alerts
|

Variability of cutaneous and nasal population levels between patients colonized and infected by multidrug-resistant bacteria in two Brazilian intensive care units

Abstract: Objective:To compare cutaneous and nasal population levels between patients colonized and infected by multidrug-resistant organisms in two intensive care units.Methods:A prospective cohort study was performed in adult intensive care units of two hospitals in Belo Horizonte, Brazil (April 2012 to February 2013). Clinical and demographic data were first collected by reviewing patients’ charts. Then, samples collected with nasal, groin, and perineum swabs were cultivated in selective media for 48 h at 37°C. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 16 publications
0
6
1
4
Order By: Relevance
“…In the present study 17.5% of isolated strains were resistant to mupirocin, which is comparable with other report [ 37 ]. Although studies have reported resistance to the newer antimicrobial agents such as linezolid and vancomycin [ 38 ], in the present study none of the isolates were resistant to these antibiotics.…”
Section: Discussioncontrasting
confidence: 64%
“…In the present study 17.5% of isolated strains were resistant to mupirocin, which is comparable with other report [ 37 ]. Although studies have reported resistance to the newer antimicrobial agents such as linezolid and vancomycin [ 38 ], in the present study none of the isolates were resistant to these antibiotics.…”
Section: Discussioncontrasting
confidence: 64%
“…Na avaliação da microbiota de populações saudáveis, a mucosa nasal e a virilha foram identificadas entre os pontos mais consistentes em relação à composição e à estrutura da comunidade microbiana em um estudo de caracterização da variação temporal da microbiota 21 .…”
Section: Discussionunclassified
“…Os bacilos gram-negativos são amplamente descritos na literatura como um dos principais microrganismos causadores de colonização e infecção nas instituições hospitalares. Vários estudos têm relatado a presença desse microrganismo, com cepas resistentes, presentes na pele de pacientes hospitalizados em UTI, com destaque para recuperação desses microrganismos nas regiões de virilha e em poucos estudos relatando a presença na axila 20,21,23,24 .…”
Section: Discussionunclassified
See 2 more Smart Citations